(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
To know the reality of nurses in the nursing care for the person with head and neck oncological wound. Methods: Descriptive exploratory study with a qualitative approach. The semi-structured interview occurred in July 2017 with 12 nurses from a cancer reference center in south of Brazil. The data were submitted to the thematic analysis proposed by Minayo. Results: Nurses perform comprehensive care based on scientifi c knowledge to choose an appropriate therapy in the treatment of the wound. The permanent education and the existence of the specialized team facilitate the practice. The diffi culties, when its appear, involve the therapeutic choice, the continuity of the home treatment and the control of the symptoms of the oncological wound. Nurses recognize its work as essential, rewarding and satisfying for bringing improved quality of life to people. Conclusion: The objective of the study was reached, highlighting the essential role of nurses and the benefi ts of continuing education. It is reaffi rmed that a specialized team and a stomatherapist nurse are fundamental for the quality and resolution of nursing care for oncological wounds.